An Investigation of Push and Pull Motivations of Visitors to Private Parks: The Case of Araluen Botanic Park - Phau, Ian; Lee, Sean; Quintal, Vanessa (Sage Publications Ltd., 2013)
This exploratory study aims at closing an inherent gap in the literature on research on private parks. Specifically, the aim of this study is threefold: (a) to identify the push and pull factors that influence decisions to visit private parks; (b) to examine the differences in these push and pull factors for different sociodemographic groups; and (c) to investigate the interrelationships among these push and pull factors. Data were collected from 228 visitors who were intercepted at various locations in a private park. The survey instrument assessed the reasons for visiting the park (push factors) and evaluated how well the park performed on a series of selected park attributes (pull factors). The results of a factor analysis revealed three push factors and three pull factors. Other analyses included an evaluation of the interrelationship between these factors in terms of different sociodemographic subgroups and a general correlation analysis on the interrelationship among push and pull factors. This study provides useful managerial and practical implications for park managers, policymakers and communication strategists to gain an understanding of how push and pull factors affect tourists and their choice of private parks.